A vallásos spiritualitás elmélyítése a tanárképzésben - GORBAI, Gabriela (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2015)
Reflecting to Religious Spirituality in Teacher Training. We think that during the training of teachers (beside their professional and methodological formation) we have to enhance their sense of vocation, dedication, and, as a result, to enhance their personal development. The Dutch researcher F. A. Korthagen, in the so-called onion-model has shown that within the individual there are several levels that can be affected, and in his opinion every single level can give us an answer to the question concerning the most important qualities of a good teacher. These perceptions can and must be used in parallel during teacher training. The model touches some relatively new research areas, such as the professional identity and vocation of the teachers. This is why we consider that it can be used as a framework for the development of future religion teachers. In this study we argue that Korthagen’s original onion-model should be completed with a new level, which is essential from the perspective of a religion teacher’s profile. Considering this specific profile of competence, the new level is that of religious spirituality, meaning the accomplishment of professional identity and missions.